Derek C. Maus and James J. Donahue. Post-Soul Satire: Black Identity after Civil Rights. Jackson: UP of Mississippi, 2014. - Jacinta Yanders (Studies in 20th & 21st Century Literature, 2017)
Review of Derek C. Maus and James J. Donahue. Post-Soul Satire: Black Identity After Civil Rights. Jackson: UP of Mississippi, 2014.
Keywords: Satire; humor; African American studies; comics; film; television; theater